Assessment and clinical management of internal contamination. (1st December 2022) - Dainiak, Nicholas; Albanese, Joseph
Abstract: Internal contamination by radionuclides may occur through inhalation, ingestion and absorption through the skin or subcutaneous tissue. The clinical management of internalized radionuclides requires the integration of clinical signs and symptoms with dose estimates in biological tissues obtained from the face, nose, sputum, urine, faeces and/or skin. The assessment of ingested radionuclides includes bioassays of urine and faeces, and if available, whole body counting for radionuclides that emit penetrating x-rays or gamma-rays. An estimate of intake dose may be made at the time of initial patient evaluation by measuring radioactivity, converting counts/minute to depositions/minute with a specific gamma-ray constant, and comparing the amount to its annual limit on intake, clinical decision guide or derived reference level. Since nobody dies from internal contamination per se, medically unstable patients should be stabilized before addressing internal contamination. Whenever possible, internal contaminants should be physically removed as soon as possible after exposure. For inhaled internal contaminants, radionuclide-specific therapy may include the administration of an ion exchange resin (i.e. Prussian blue, PB) or chelating agent (i.e. diethylenetriamine pentaacetate, DTPA, that binds to radioactive plutonium, americium, and curium), or the physical removal of insoluble particles with a high activity radionuclide ( 192 Ir, 90 Sr, 210 Po) by bronchioalveolar lavage. Decorporation with PB, DTPA and other agents is used to enhance excretion. The treatment of wounds contaminated with an actinide includes gentle irrigation, surgical excision of contaminated tissue and DTPA. The averted dose (i.e. the total effective dose averted by therapy) may be calculated for each exposure route.